Immunomodulatory effect of fractions of ethanolic extract from emblica officinalis (amla) fruit pulp in mice - Senthil Kumar P K (Department of Pharmacology and Toxicology, College of Veterinary and Animal Sciences, 2005)
The immunomodulatory activity of acetone soluble and acetone insoluble fractions of ethanolic extract of Emblica officinalis was investigated in the present study. The extracts were also qualitatively tested for the presence of various active principles. One hundred and forty four male swiss albino mice were used to assess humoral and cellular immunity by feeding the extracts at dose level of 200 mg per kg body weight for 19 days. Few animals were also administered with dexamethasone at the dose rate of 0.75 mg per kg body weight intra peritoneally for seven days before the start of the experiment to suppress the immune system and thereby to study the effect of extracts on immunosuppressed animals also. The control group received vehicle alone (five percent gum acacia).